Literature Review of Inventory with Probabilistic Economic Order Quantity (EOQ) - Annisa Wirrdiana Yuniasih; Nur Rohmah Lufti A'yuni (Politeknik STMI Jakarta, 2024)
In the current era of global competition, many trading companies compete to meet consumer needs. This competition causes the level of demand between companies to fluctuate greatly, resulting in problems in the company's inventory system for goods or products. Inventory problems that often occur in a company include over stock, stock out, underproduction, overproduction, back log, and inventory that is not in line with company targets. This inventory problem is one of the things that must be overcome by controlling mathematically using methods that suit needs. One method that assumes this fluctuating demand used a model Economic Order Quantity (EOQ) Probabilistic. Therefore, this study aims to examine the use of Probabilistic EOQ in controlling company inventory and find out how much influence the use of this model has on company inventory. This study uses the method Systematic Literatur Review or SLR with a qualitative model that combines several literature articles as a reference for the study. The study produced several important notes on the use of the Probabilistic EOQ model. This model aims to optimize total inventory costs with the assumption that demand for products or goods is very fluctuating. This model assumes that the data is normally distributed with a waiting time or lead time as a basis for decision making in calculating optimal inventory. Apart from that, other supporting methods are needed to strengthen calculations in overcoming inventory shortages, such as safety stock or safety supplies and reoder point. The research results show that this method can be used on various types of food and non-food items. Apart from that, this method is considered to be able to reduce total inventory cost or total inventory costs.